Body weight and weight perception among African and Caribbean university students: Correlation with depression symptoms. Issue 5 (23rd October 2017) - Pengpid, Supa; Peltzer, Karl
Abstract : The aim of the study was to investigate the association between body weight, weight perception, and depressive symptoms in African and Caribbean university students. In a cross-sectional survey the total sample included 4 964 undergraduate university students (mean age 21.8, SD = 3.4, age range = 18-30 years) from five African and three Caribbean countries. Data on the students' actual and perceived body weight, as well as depression symptoms, were collected. In logistic regression, perceived rather than measured overweight predicted depressive symptoms in male students with normal weight. For female students, perceived overweight predicted depression symptoms regardless of actual body weight. Male students who overestimated their body weight were at greater risk of depressive symptoms. Body weight self-perceptions appear to influence experience of mood disorder among African and Caribbean country students.